The Eloquence of Ellipsis Style in the Quran's Talk about the Quran; Reading in Some Meccan Verses | بلاغة أسلوب الإيجاز في حديث القرآن عن القرآن؛ قراءة في بعض الآيات المكية - Ahmadi Usman Sirathan; Yogi Sofiyullah (Al-Zahra : Journal for Islamic and Arabic Studies, 2019)
The purpose of this study is to reveal the concept of ellipsis of the Arabic eloquence in the Holy Quran and the views of it in some of the Meccan Verses in which ellipsis exist. By applying the analytical method, this article conducts an analysis on patterns of Ellipsis in the Quran’s talk about the Quran in some those Meccan verses. This article, therefore, finds that these verses contain two types of Ellipsis’ style; Îjâz al-Qaṣr (Ellipsis of Shortness) and Îjâz al-Ḥadzf (Ellipsis of Deletion). In the end, furthermore, the result of this article focusing on the analysis of some Meccan verses proves the excellence of the Quran to other Arabic structure styles.